The fall migratory movements of Bank Swallows, Riparia riparia: fly-and-forage migration? - Tara L. Imlay (Resilience Alliance, 2020)
Seasonal migration is an important part of the annual cycle for migratory birds, and it is associated with large time and energy expenditures. One migration strategy used by many raptors and aerial foragers is fly-and-forage migration. Fly-and-forage migrants combine migratory flights with foraging to maximize travel speeds. We examine the fall migratory movements of a declining population of Bank Swallows Riparia riparia that breed in Atlantic Canada, and winter between northern Argentina and southern Brazil. We tagged breeding adults with small VHF transmitters in 2014, 2015, and 2018, and tracked them with the Motus Wildlife Tracking System. For each individual we determined a departure date (last detection at the breeding colony), a departure bearing, the broad-scale migratory pathway (east or west of the Adirondack Mountains), and the pace of the migratory journey. Bank Swallows departed from their breeding colonies throughout July and August and most individuals departed in a southwest to westerly direction, consistent with their subsequent migratory pathway along the Atlantic Coast. The pace of the migratory journey was slower than that observed for other migratory passerines, suggesting individuals used stopover sites during migration and/or foraged while migrating. Travel speeds were also slower for female, compared to male Bank Swallows, possibly because of sex-related differences in refueling and/or carry-over effects from the breeding season. Collectively, the results suggest that Bank Swallows use a fly-and-forage migration strategy, and fall migration movements are consistent with an energy-limiting strategy.